Identifying the Objectives of the Lower Secondary Social Studies Curriculum Based on 21st-Century Skills - Kohi Sowme, Farahnaz; Baghaei , Hossein; Daneshvar Heris , Zarrin (Assessment and Practice in Educational Sciences, 2025)
This study aims to identify and articulate the objectives of the lower secondary social studies curriculum based on the competencies required for 21st-century skills. A qualitative research design was adopted, consisting of two sequential phases. In the first phase, a research synthesis method was used to review 132 national and international sources related to 21st-century skills and social studies curricula, from which 44 studies were purposively selected based on defined inclusion criteria. In the second phase, semi-structured interviews were conducted with 16 curriculum specialists and senior educational group leaders in social studies using purposive sampling until data saturation was reached. Data collection tools included a researcher-designed coding worksheet for the synthesis phase and a semi-structured interview guide. Thematic analysis and Roberts’ six-step synthesis model were used for data analysis. The findings revealed 14 initial themes including enhancing effective communication, developing active listening, fostering group collaboration, promoting social and cultural adaptability, cultivating responsibility, and encouraging critical thinking. These themes were categorized into three broader skill domains: social skills, intercultural communication skills, and life-career readiness. All of these were integrated under one overarching category—education of life, communication, and career skills grounded in 21st-century competencies. The study also highlighted the importance of learner agency, ethical responsibility, and practical employability as key curriculum objectives. The study underscores the necessity of revising the lower secondary social studies curriculum to systematically incorporate 21st-century skills. The proposed objectives serve as a guiding framework for curriculum designers, educators, and policymakers to align educational practices with the evolving demands of society, the labor market, and democratic participation in a globalized world.